PENGARUH MODEL PEMBELAJARAN JUCAMA TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IX MTSN 02 TAKENGON - umar, ali (Math Educa Journal, 2020)
This study supports 1). Knowing the differences in problem-solving abilities in students before and after being taught with the JUCAMA learning model; 2). Knowing students' problem solving skills between before and after being taught with the JUCAMA learning model in high initial students; 3). Knowing students' problem solving skills between before and after being taught with the JUCAMA learning model in students with low initial ability; 4). Conversation between initial ability and learning model on students' problem solving. This study uses quantitative research with a quasi-experimental type of research. The results showed 1). 95% (16.67> 9.98, tcount = 7.816> t table = 1.71; 2). The average problem solving ability of students in early ability students was higher after being taught with the JUCAMA learning model than before at 95% confidence level (16.09> 13.72, tcount = 15.53> ttable = 1.81); 3. The average problem solving ability of students in early ability students is lower after being taught with the JUCAMA learning model than before at 95% confidence level (10.31> 7.25, tcount = 5.21> ttable = 1.75). While the results of the interaction test showed there was no interaction between the initial ability and the learning model on the ability to solve students' problems at a 95% confidence level (Fcount = 0.29 <Ftable = 1.35), so that the JUCAMA learning model was suitable for use with diverse abilities . Based on the research it was also found that students needed more time than usual to solve problems of type solving problems.